2017
DOI: 10.3923/jms.2017.117.125
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Caspase-3 mRNA Gene Expression Activity in Amyloid Beta-induced Alzheimer’s Disease Rats

Abstract: is an International, peer-reviewed scientific journal that publishes original article in experimental & clinical medicine and related disciplines such as molecular biology, biochemistry, genetics, biophysics, bio-and medical technology. JMS is issued four times per year on paper and in electronic format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In the current study, the up-regulation of the caspase-3 gene in group II indicated the apoptotic effects of IBO acid on rat's hippocampus tissues. The ndings of Kamelia et al (Kamelia et al 2017) indicated that the accumulation of amyloid-beta exhibited overexpression of caspase-3.…”
Section: )mentioning
confidence: 97%
“…In the current study, the up-regulation of the caspase-3 gene in group II indicated the apoptotic effects of IBO acid on rat's hippocampus tissues. The ndings of Kamelia et al (Kamelia et al 2017) indicated that the accumulation of amyloid-beta exhibited overexpression of caspase-3.…”
Section: )mentioning
confidence: 97%
“…Apoptosis further affects AD pathologies through the catalytic activities of caspases. For example, activated caspase-3 can directly cleave amyloid precursor protein (APP), producing additional APP fragments with cytotoxicity [25]. These fragments accumulate in the cortical and hippocampal regions of the brain as AD progresses.…”
Section: Functional Consequences Of Neural Cell Death In Ad 21 Pathol...mentioning
confidence: 99%
“…Caspase-3 cleaves the subunits of AMPA receptors to inhibit neuronal responsiveness to the neurotransmitter, glutamate. As a result, AD patients and AD transgenic mouse models show severe spatial learning and memory deficits due to neuronal loss and neurodegeneration [25,27].…”
Section: Functional Consequences Of Neural Cell Death In Ad 21 Pathol...mentioning
confidence: 99%